The Religious Tolerance in Weaving National Unity and Cohesion - Afriansyah, Donal; Ghozali, Muhammad Bahri; Sam’un, Muhammad Arif; Maksudi (IJESS International Journal of Education and Social Science, 2025)
Religious tolerance constitutes an essential foundation for maintaining the unity and cohesion of Indonesia’s pluralistic society. This study provides an in-depth examination of the nature of interreligious tolerance, its relevance to religious, cultural, humanitarian, social, historical, and ethical values, as well as the current challenges in its implementation within society. In Indonesia, religious diversity is not merely a social reality but also a constitutional mandate that affirms freedom of religion as a fundamental right of every citizen. The teachings of Islam and other religions position mutual respect as a fundamental principle in social interactions. However, various incidents of intolerance indicate that there remains a gap between ideal norms and everyday practices. Through a comprehensive understanding of the concept of tasamuh (tolerance), cultural values, and historical exemplars, this research underscores the importance of strengthening religious moderation as a strategy to foster social harmony. Religious moderation is viewed as a collective endeavor involving the government, religious leaders, and the broader community to instill mutual respect without compromising each individual’s core beliefs. Thus, tolerance is not merely a passive compromise but an active effort to build sustainable social harmony in pursuit of a sovereign, just, and civilized nation.